2023
DOI: 10.3389/fonc.2023.1105117
|View full text |Cite
|
Sign up to set email alerts
|

FDXR drives primary and endocrine-resistant tumor cell growth in ER+ breast cancer via CPT1A-mediated fatty acid oxidation

Abstract: BackgroundThe majority of breast cancers (BCs) expressing estrogen receptor (ER) have shown endocrine resistance. Our previous study demonstrated that ferredoxin reductase (FDXR) promoted mitochondrial function and ER+ breast tumorigenesis. But the underlying mechanism is not clear.MethodsLiquid chromatography (LC) tandem mass spectrometry (MS/MS)-based metabolite profiling was utilized to reveal the metabolites regulated by FDXR. RNA microarray was utilized to determine the potential downstream targets of FDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Most of the included genes have been reported to exert protumor functions and are associated with prognosis in a variety of malignant diseases, including BC (55)(56)(57)(58)(59). For example, CPT1A, the rate-limiting enzyme during FAO, has been found to promote cell proliferation and survival in luminal BC (60,61). Serum CPT1A levels are also associated with the tumor burden of BC (62).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the included genes have been reported to exert protumor functions and are associated with prognosis in a variety of malignant diseases, including BC (55)(56)(57)(58)(59). For example, CPT1A, the rate-limiting enzyme during FAO, has been found to promote cell proliferation and survival in luminal BC (60,61). Serum CPT1A levels are also associated with the tumor burden of BC (62).…”
Section: Discussionmentioning
confidence: 99%
“…Given that CPT1A-enhanced FAO can promote the acquisition of malignant phenotypes such as cell proliferation and tamoxifen resistance in ER-positive BC cells, CPT1A-FAO might be an effective target for overcoming tamoxifen resistance in BC cells. Recent reports have indicated that pharmacologic inhibition of CPT1A and FAO could prevent ER-positive BC tumour growth and cell proliferation [ 10 , 15 , 39 , 40 ]. In the present study, we demonstrated that inhibition of CPT1A-mediated FAO with a CPT1 inhibitor re-sensitised ER-positive BC cells to tamoxifen therapy, which broadened the therapeutic effects of CPT1A/FAO inhibitors in tumours.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to epigenetic control, the crosstalk between factors involved in different metabolic processes can regulate CPT1A activity. A recent study revealed that a mitochondrial flavoprotein promoted CPT1A transcription levels by modulating mitochondrial function [ 40 ]. This finding inspired us to conclude that cellular metabolic processes might also exert a regulatory effect on CPT1A expression in ER-positive BC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Etomoxir, a well-established CPT1A inhibitor, demonstrates notable antitumour effects across various cancer models. It exhibits efficacy in decreasing the growth and proliferation of endocrine-resistant breast cancer cells by inhibiting FAO [94]. In prostate cancer, etomoxir suppressed cell growth by reducing both FAO and androgen receptor expression levels [93].…”
Section: Altered Fatty Acid Oxidationmentioning
confidence: 99%